2014
DOI: 10.1155/2014/718690
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia after Gastrectomy in a Patient with Cervical Disc Herniation: A Case Report and Review of Literature

Abstract: Paraplegia is a rare postoperative complication. We present a case of acute paraplegia after elective gastrectomy surgery because of cervical disc herniation. The 73-year-old man has the medical history of cervical spondylitis with only symptom of temporary pain in neck and shoulder. Although the patient's neck was cautiously preserved by using the Discopo, an acute paraplegia emerged at about 10 hours after the operation. Severe compression of the spinal cord by herniation of the C4-C5 cervical disc was diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another strategy to provide OLV is inserting an endotracheal tube (ETT) into the dependent bronchus. Considering that the low-pressure cuff has a lower risk of mucosal injury even applying increased volume of air to the cuff, this seems to be a better choice for patients with TBM [ 7 , 8 ]; however, it should be noted that for a patient with TBM, the cuff site will be very inclined to be dilated and subsequently narrowed due to the fibrous tissue formation. It was thus suggested that intubation the trachea with an uncuffed tube together with throat packing to reduce the risk of gas leakage and aspiration [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy to provide OLV is inserting an endotracheal tube (ETT) into the dependent bronchus. Considering that the low-pressure cuff has a lower risk of mucosal injury even applying increased volume of air to the cuff, this seems to be a better choice for patients with TBM [ 7 , 8 ]; however, it should be noted that for a patient with TBM, the cuff site will be very inclined to be dilated and subsequently narrowed due to the fibrous tissue formation. It was thus suggested that intubation the trachea with an uncuffed tube together with throat packing to reduce the risk of gas leakage and aspiration [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tracheobronchomegaly (TBM) first described by Mounier Kuhn in 1932 [ 1 ] is a very rare disorder characterized by marked tracheobronchial dilation and flaccidity with diverticularization from the severe atrophy of elastic fibers with thinning of the muscularis mucosa in the central airway [ 2 – 4 ] .The airway management of a patient with TBM can be challenging and more complex for one-lung ventilation (OLV). To the authors’ knowledge, very few cases with TBM receiving OLV were reported [ 5 – 8 ]. Here, the authors presented a patient with TBM receiving left lower lobectomy.…”
Section: Introductionmentioning
confidence: 99%